2019
DOI: 10.1002/adfm.201904956
|View full text |Cite
|
Sign up to set email alerts
|

Fused Cyclopentadithienothiophene Acceptor Enables Ultrahigh Short‐Circuit Current and High Efficiency >11% in As‐Cast Organic Solar Cells

Abstract: A new method to synthesize an electron-rich building block cyclopentadithienothiophene (9H-thieno-[3,2-b]thieno[2″,3″:4′,5′]thieno[2′,3′:3,4] cyclopenta[1,2-d]thiophene, CDTT) via a facile aromatic extension strategy is reported. By combining CDTT with 1,1-dicyanomethylene-3-indanone endgroups, a promising nonfullerene small molecule acceptor (CDTTIC)is prepared. As-cast, single-junction nonfullerene organic solar cells based on PFBDB-T: CDTTIC blends exhibit very high short-circuit currents up to 26.2 mA cm −… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 42 publications
0
23
0
Order By: Relevance
“…34 Matching with wide bandgap polymer donors such as PBDB-T or PM6, the resulting all-PSCs showed a high J sc of 16.05-17.1 mA cm À2 and impressive PCEs in the range of 9.19-11.2%. 23,34 However, compared to high-performance SM-acceptors with broader absorption spectra and a higher absorption coefficient and thus a high J sc of the resulting PSCs, 1,3,[39][40][41][42] PZ1 still exhibits limited J sc when implemented in all-PSCs. For example, the SM-acceptor Y5 shows an absorption onset wavelength of B890 nm with a high absorption coefficient of B1.24 Â 10 5 cm À1 due to its unique benzothiadiazole (BT)-fused A 1 -DA 2 D-A 1 -type building block.…”
Section: Introductionmentioning
confidence: 99%
“…34 Matching with wide bandgap polymer donors such as PBDB-T or PM6, the resulting all-PSCs showed a high J sc of 16.05-17.1 mA cm À2 and impressive PCEs in the range of 9.19-11.2%. 23,34 However, compared to high-performance SM-acceptors with broader absorption spectra and a higher absorption coefficient and thus a high J sc of the resulting PSCs, 1,3,[39][40][41][42] PZ1 still exhibits limited J sc when implemented in all-PSCs. For example, the SM-acceptor Y5 shows an absorption onset wavelength of B890 nm with a high absorption coefficient of B1.24 Â 10 5 cm À1 due to its unique benzothiadiazole (BT)-fused A 1 -DA 2 D-A 1 -type building block.…”
Section: Introductionmentioning
confidence: 99%
“…15 These high performance characteristics have been attributed in part to its long wavelength absorption onset (B900 nm) and complementary donor and acceptor absorption, large absorption extinction coefficients, and moderate HOMO and LUMO energy offsets. 5,[16][17][18][19] More in depth studies by Karki et al and Perfigon-Toro et al have identified several additional factors which may be critical to this blend's high performance, including efficient charge generation with barrierless CT state dissociation, and a nanomorphology favourable for charge separation. 15,20,21 The achievement of both high EQEs over 80% (up to 900 nm) and a low voltage loss in this blend has been highlighted as particularly remarkable.…”
mentioning
confidence: 99%
“…With those in mind, tremendous progresses have been made by many groups. Some representative IR‐absorbing non‐fullerene acceptors with narrow bandgaps that have been synthesized include: Y1 (1.44 eV), [ 21 ] CDTTIC (1.44 eV), [ 22 ] DOC2C6‐2F (1.42 eV), [ 23 ] AOIC (1.39 eV), [ 24 ] FNIC2 (1.38 eV), [ 25 ] AQx‐2 (1.35 eV), [ 26 ] Y6 (1.33 eV), [ 27 ] FOIC (1.32 eV), [ 28 ] BT‐CIC (1.3 eV), [ 29 ] F8IC (1.27 eV), [ 30 ] COi8DFIC (1.26 eV), [ 31 ] IEICO‐4F (1.24 eV), [ 32 ] DTPC‐DFIC (1.21 eV). [ 33 ] Combined with large/medium bandgap donors, single‐junction devices based on these acceptors can achieve very high J SC (26–28 mA cm −2 ).…”
Section: Main Factors For High‐performance Devicesmentioning
confidence: 99%